Pengaruh Kepercayaan, Kualitas Informasi Dan Persepsi Resiko Terhadap Keputusan Pembelian Di Media Sosial Instagram (Studi Kasus Pada Mahasiswa FEB UNISMA) - Ahmad Faruq Al Hafiz; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract On online shopping sites, there are many fictitious online sellers who market fictitious products as well. A buyer must first check the existence of an online seller. Usually on an online shopping site, the site will display information about sellers whose